Development of a Portable Electronic Nose System for the Detection and Classification of Fruity Odors - Tang, Kea-Tiong (Molecular Diversity Preservation International (MDPI), 2010)
In this study, we have developed a prototype of a portable electronic nose (E-Nose) comprising a sensor array of eight commercially available sensors, a data acquisition interface PCB, and a microprocessor. Verification software was developed to verify system functions. Experimental results indicate that the proposed system prototype is able to identify the fragrance of three fruits, namely lemon, banana, and litchi.